Limited Protection from a Pathogenic Chimeric Simian-Human Immunodeficiency Virus Challenge following Immunization with Attenuated Simian Immunodeficiency Virus - Lewis, Mark G. (American Society for Microbiology, 1999)
Two live attenuated single-deletion mutant simian immunodeficiency virus (SIV) constructs, SIV(239Δnef) and SIV(PBj6.6Δnef), were tested for their abilities to stimulate protective immunity in macaques. During the immunization period the animals were examined for specific immune responses and virus growth. Each construct generated high levels of specific immunity in all of the immunized animals. The SIV(239Δnef) construct was found to grow to high levels in all immunized animals, with some animals remaining positive for virus isolation and plasma RNA throughout the immunization period. The SIV(PBj6.6Δnef) was effectively controlled by all of the immunized animals, with virus mostly isolated only during the first few months following immunization and plasma RNA never detected. Following an extended period of immunization of over 80 weeks, the animals were challenged with a pathogenic simian-human immunodeficiency virus (SHIV) isolate, SIV(89.6PD), by intravenous injection. All of the SIV(239Δnef)-immunized animals became infected with the SHIV isolate; two of five animals eventually controlled the challenge and three of five animals, which failed to check the immunizing virus, progressed to disease state before the unvaccinated controls. One of five animals immunized with SIV(PBj6.6Δnef) totally resisted infection by the challenge virus, while three others limited its growth and the remaining animal became persistently infected and eventually died of a pulmonary thrombus. These data indicate that vaccination with attenuated SIV can protect macaques from disease and in some cases from infection by a divergent SHIV. However, if animals are unable to control the immunizing virus, potential damage that can accelerate the disease course of a pathogenic challenge virus may occur.